The Impact of the Visual Teaching Strategy Using Infographics on the Achievement of Fifth-Grade Science Students in Physics and Their Critical Thinking - Dr. Ali Salem Suleiman Al-Suwaidi (Peerian Journals Publishing, 2025)
The current study aims to investigate the effect of visual teaching strategy using infographics on the academic achievement of fifth-grade science students in physics and their critical thinking. The sample consisted of (82) male students from the fifth-grade science class at Al-Sharqiya Preparatory School for Boys for the academic year (2024-2025) in the second semester. The school was intentionally selected because it contains more than four classes, in addition to the school administration's cooperation in the experiment and the subject teacher's participation. Two classes were randomly selected: the first as an experimental group, which was taught using the visual teaching strategy with infographics, and the second as a control group, which was taught using the traditional method
Keywords: Fifth; grade science; visual teaching strategy with nfographics